Theatre and Psychoanalysis: or Jung on Martin Crimp's Stage: “100 Words” - Solange Ayache (Sillages Critiques)
This article explores Martin Crimp’s use of Jung’s word association test in his masterpiece Attempts on Her Life (1997). In scenario 11, the playwright reproduces the list of one hundred stimulus words devised in 1909 by the psychoanalyst to test a patient’s mental health. Our point is that this “collage” of disarticulated words inserted by Crimp into the dialogue of three anonymous art critics ironically emphasizes the absence of the main character, the suicidal artist, and her refusal to undergo “treatment.” Anne’s posthumous silence both ignores the psychoanalyst’s trigger words and mocks the critics’ conflicting opinions. By foiling these “attempts on her life”, her aphasia reflects the vain pretensions of language and points both at the failure of the scientific purpose of psychoanalysis and at the “pointlessness” of the intellectual debate. Crimp’s collage itself is a criticism of the temptation to make uncompromising statements about one’s life and motives. While the critics’ debate ends in disagreement, the scientific voice faces its own loneliness and becomes a pure dramatic event. A similar resort to psychoanalysis and psychiatry can be found in Sarah Kane’s 4.48 Psychosis (2002): in these “theatres of the mental space,” both authors turn either the clinical voice of the doctor or the neurotic voice of the patient into a self-referential source of vocal stage poetry displaying the bare materiality of words and the disapearance of the subject.